Respons Curvularia lunata Penyebab Penyakit Bercak Daun Kelapa Sawit terhadap Berbagai Fungisida - Agus Susanto; Agus Eko Prasetyo (Jurnal Fitopatologi Indonesia, 2013)
Leaf spot disease of oil palm caused by Curvularia sp. is the major disease in nursery. Implementation of best nursery practices is the key to prevent it. Generally, fungicides are used only if epidemic of leaf spot diseases occur in the field. The objectives of this research were to determine causal agent of leaf spot disease of oil palm and the potential alternative weed host around the nursery, to select suitable fungicides, and to study the effect of fungicides rotation to disease incidence. The results showed that the causal agent of leaf spot disease of oil palm was Curvularia lunata. The fungus was also found on grasses, Cyperus rotundus and Imperata cylindrica. Difeconazol, copper oxide, and propineb suppressed leaf spot disease in nursery. Application of fungicide by rotation between difeconazol and copper oxide with frequency every 10 days suppressed the development of leaf spot disease of oil palm in the nursery.